Training and implementation of the environmental, economic, and legal development policy of the regions: main practice-oriented approaches - Bukanov, Hryhorii; Skakovska, Svitlana; Kulbaka, Viktor; Sytnichenko, Olena; Kulbaka, Olesia (Cuestiones Políticas, 2020)
The article explores the possibilities of practice-oriented approaches in public administration, in the field of training and implementation of the ecological development policy of the regions, between areas, modern social and economic conditions instead. The methodological basis of the study consists of general scientific methods of cognition and social processes (analysis, synthesis, generalization, classification) and sociological methods for obtaining empirical data. The forms of optimization of public administration in the field of training and implementation of the ecological development policy of the regions are concluded, manifested in the practice-oriented approaches select in the following directions: from the framework outside responsibility and legal in the field of environmental protection; strengthening the role of economic mechanisms and environmental management tools in the regions; modernization of the public and state administration system in the field of environmental protection, and; Dissemination of an instrument of cross-sectoral social collaboration in the field of training and implementation of ecological development policy.